The Effects of Flexible Manufacturing Capabilities and Logistics Capabilities on Firm Performance: Mass Customization as a Dual Mediator - LEE, Shyh-Hwang; CHEN, Ching-Yaw; LEE, Yu-Je (Asian Journal of Empirical Research, 2013)
This study aims to verify the impacts of flexible manufacturing capabilities and logistics capabilities, with mass customization as a dual mediator, on the performances of Taiwan photoelectric companies. Respondents are from department supervisors and managers. Structural equation modeling (SEM) is used to fit the overall pattern of the structural model and measurement mode in this study and followed by applying Sobel Test, Bootstrapping, and Mackinnon PRODCLIN2 method to verify the effect of dual mediator. Results show that: (1) flexible manufacturing capabilities have a significant positive impact on mass customization; (2) mass customization have a significant impact on firm performances; (3) flexible manufacturing capacities also significantly impact on firm performances; (4) logistics capabilities positively impact on mass customization and (5) logistics capabilities have a significant impact on firm performances. Therefore, “mass customization” plays an important role as a dual mediator in the impact pattern of flexible manufacturing capabilities and logistics capabilities on firm performances.